Implementasi Pendidikan Karakter Religius dan Mandiri Melalui Pembiasaan Berbasis Budaya Sekolah di SD Negeri 03 Kabawetan - Hendri Harianto; Puspa Djuwita; Abdul Muktadir (UNIB Press, 2023)
This study aims to explain planning, reveal and describe the implementation and evaluation of the implementation of religious and independent character education through habituation based on school culture in SD Negeri 03 Kabawetan. This type of research is a qualitative descriptive research. The subjects in this study were teachers, students and the principal of SD Negeri 03 Kabawetan, Kepahiang Regency. The research instruments are interviews, observation, and document study. The data analysis technique used is interactive model data analysis, including: data collection, data condensation, data presentation, and drawing conclusions or verification. The results showed that: 1) Planning for the implementation of religious and independent character values ​​through habituation based on school culture at SD Negeri 03 Kabawetan has gone quite well (2) Implementation has gone quite well through routine activities, programmed activities, and spontaneous activities (advising participants educate those who break the rules and provide direct examples, so they don't do it again). (3) Evaluation of the implementation of character values ​​is still lacking because no follow-up has been carried out on the school culture program on religious and independent character values.